APLIKASI PENDATAAN JALAN BERLUBANG SKPD-TP DINAS BINAMARGA PROVINSI JAWA TIMUR PPK WILAYAH PROBOLINGGO-LUMAJANG-TUREN-KEPANJEN BERBASIS ANDROID - Habibi, Ahmad; Affandi, Luqman; Susilo, Antonius Duty (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
The road is one of the important aspects in the various aspects of human life. The authorities inthe construction or repair of the road is the Department of Public Works. One of them is theregional work units - Assistance (SKPD-TP) Department of Highways East Java ProvinceCommitment Officer (CO) Region Probolinggo-Malang-Turen-Kepanjen. One of theimprovements made are repair Potholes. Before improvement, first of all performed the hollowstreets of the data collection.Reviews their reviews with smartphone technology (smart phones).First of all the which is based smartphone android that can be the perfect solution for themanufacture of standard software, because Android provides an open platform. Some facilitiesmay be developed is a camera, Global Positioning System (GPS), and the network. The aim inthis research is the establishment of the recording application SKPDs hollow-PT Department ofHighways Probolinggo, East Java PPK - Lumajang - Turen - Kepanjen Regional. ApplicationsAndroid-based registrar Potholes  Able  to  simplify  the process of data Potholes on regionalwork units - Assistance (SKPD-TP) Department of Highways East Java Province CommitmentOfficer (CO) Probolinggo-Lumajang-Turen-Kepanjen Region.Keywords :Potholes, Android